Pharmacokinetics and pharmacodynamics of ropinirole in patients with prolactinomas. Issue 2 (22nd November 2018) - Liu, Sihang; Hu, Can; Peters, Jane; Tsang, Amanda; Cremers, Serge; Bies, Robert; Page‐Wilson, Gabrielle
Abstract : Aims: Treatment of prolactinomas with ergoline dopamine agonists can be complicated by intolerance and resistance. This study investigated the pharmacokinetics and pharmacodynamics of the nonergot dopamine agonist ropinirole, to assess its therapeutic potential as a novel therapy for prolactinomas. Methods: Five female subjects with prolactinomas participated in this dose–response study. Subjects received up to three doses of ropinirole (0.5, 1.0 and 2.0 mg), each on separate occasions. Frequent blood samples for prolactin and ropinirole were collected for 24 h following drug administration. Data were analysed using noncompartmental and compartmental pharmacokinetic–pharmacodynamic (PKPD) techniques. Results: Seven 24‐h curves revealed increased systemic drug exposure with increasing ropinirole doses. Ropinirole concentrations peaked at 4.4 ± 2.7 h and exhibited a half‐life of 5.8 ± 1.7 h. A dose‐dependent prolactin nadir occurred 4.4 ± 1.2 h after drug intake and prolactin concentrations transiently normalized in two of five subjects. PKPD modelling revealed that single‐dose PK of ropinirole is dose‐independent and can be described with a one‐compartment model with linear absorption and elimination. An indirect response model successfully captures the inhibitory effect of ropinirole on prolactin secretion and incorporates time‐dependent receptor desensitization for three of five subjects whose prolactin concentrations nadired before ropinirole reached Cmax . Conclusions: This data‐rich study has informed our understanding of the clinical pharmacokinetics and pharmacodynamics of ropinirole, which are successfully captured by the proposed semi‐mechanistic PKPD model. This model can be used to further investigate the PKPD of ropinirole and may facilitate the identification of optimal dose regimens for the treatment of prolactinomas and the establishment of a new therapeutic option for patients impacted by this rare disease.